Development of equipment and technological schemes to reduce emissions of sugar factory - Пономаренко, Віталій Васильович; Пушанко, Наталія Миколаївна; Пушанко, Микола Миколайович (Technology audit and production reserves, 2015)
The state of utilization of steam and gas emissions in the sugar industry is analyzed. The significant emissions at low stimulation work to reduce them are stated. One reason for this situation is the lack of cost-effective recycling of heat and chemical potentials. One of the ways to reduce emissions is to intensify the work of saturation and sulfitation devices. Data of research of saturation device with the first stage of phase contact spray and subsequent bubble are presented. The implementation of saturation process in this unit allows increasing the utilization rate of CO2 by 20 ... 25 % and improving the quality of the juice. For deeper utilization of steam and gas emissions it is proposed technological scheme, which involves pretreating beet chips by exhaust sulfur burned and carbonated gases. Such treatment would allow on the one hand minimizing thermal pollution emissions and corrosive gases and, on the other hand utilizing the energy potential of the preparation of raw materials for extraction. The equipment for this treatment is available commercially or can be produced by the sugar factory itself.